2024
DOI: 10.1002/cncr.35307
|View full text |Cite
|
Sign up to set email alerts
|

Uses and limitations of artificial intelligence for oncology

Likhitha Kolla,
Ravi B. Parikh

Abstract: Modern artificial intelligence (AI) tools built on high‐dimensional patient data are reshaping oncology care, helping to improve goal‐concordant care, decrease cancer mortality rates, and increase workflow efficiency and scope of care. However, data‐related concerns and human biases that seep into algorithms during development and post‐deployment phases affect performance in real‐world settings, limiting the utility and safety of AI technology in oncology clinics. To this end, the authors review the current po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…They also note that human biases can influence AI’s clinical use. A survey revealed that while many Korean physicians recognized AI’s usefulness in diagnosis, few were well-versed in AI, and some doubted AI’s effectiveness in unforeseen circumstances [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also note that human biases can influence AI’s clinical use. A survey revealed that while many Korean physicians recognized AI’s usefulness in diagnosis, few were well-versed in AI, and some doubted AI’s effectiveness in unforeseen circumstances [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%